Haemostatic, inflammatory and haematological biomarkers among orthopaedic patients with prolonged immobilization and risk of venous thromboembolism - Iberahim, Salfarina (2018)
Trauma and prolonged immobilization induce hypercoagulable state with thrombotic potential. Multiple studies have shown close relationship between haematological, haemostatic & inflammatory markers and post traumatic patients. The aims of this study were to investigate the changes of hypercoagulable markers (haemostatic, inflammatory and haematological parameters) in prolonged immobilized trauma patients and to determine the correlation between haemostatic parameters and inflammatory parameters (ESR, CRP) among the subjects. The association between clinical risk factors (age, sex, BMI, smoking and type of injury) and the abnormal laboratory parameters were also studied including the relationship with VTE. A prospective cohort study was conducted at Hospital University Sains Malaysia from September 2016 to July 2017. A total of 52 patients with lower limb/s fracture with age ranged from 12 to 59 years old, who required immobilization more than 7 days and received no anticoagulant prophylaxis were involved in this study. The predetermined parameters were serially measured on day 1 and day 8 of immobilization. The laboratory tests included PT, aPTT, D-dimer, Fibrinogen, AT, Protein C, Protein S, ESR, CRP and platelet count. Subjects’ characteristic and clinical risk factors (age, sex, BMI, smoking and type of injury) were recorded.